Gains from patent protection: Innovation, market power and cost savings in India - Apoorva Gupta; Joel Stiebale (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2024)
We study the effect of stronger patent protection on innovation activities of firms and firm-product level markups. Relying on cross-industry differences in the use of patents, we exploit firm-level variation in exposure to India's patent reform. For firms more exposed to stronger patent protection, we find an increase in patenting and R&D expenditure post-reform. Additionally, we estimate an increase in firm-product level markups after the reform, driven primarily by lower marginal costs rather than higher prices. Our results indicate that process innovations and output expansion contributed to these cost-savings, and incomplete pass-through accounts for a substantial part of rising markups.
Keywords: L10; O30; O31; O00; D22; 330; Intellectual property rights; patent protection; innovation; R&D; markups; patents